Static and Dynamic Tearing of Thin Steel Sheets - Aberkane, M.; Ouibrahim, A.; Pluvinage, G.; Azari, Z. (Проблемы прочности, 2003)
This paper presents the energy analysis of static mode III fracture of thin steel sheets. For dynamic tearing studies we used the Charpy test apparatus. Static tearing tests performed on three kind steel sheets indicate that the linear relationship of Mai and Cotterell is valid for specimens with a leg width W up to 30 mm. In the given range, the specific work of fracture Te is determined according to the Mai-Cotterell model. The Te kinetics is studied as a function of sheet thickness B, radius of curvature p, and loading rate V. The modified model includes a linear dependence of p versus W. Moreover, we show that variation of loading rate V from 1 to 300 mm/min has no effect on the specific work of fracture Te. A slight decrease in dynamic fracture toughness J0,d is found.